CHARACTERIZING LATE PERIOD CERAMICS OF LOWER NEGROMAYO RIVER BASIN (LUCANAS-AYACUCHO): PRELIMINARY CONTRIBUTIONS FROM THE CERAMICS OF CANICHI ARCHAEOLOGICAL SITE - Berrocal Flores, Sonia (2009)
This study is an analysis of surface ceramic collection from the archeological site of Canichi, which is located in the lower basin of the Negromayo River, in the district of Andamarca, south of the region of Ayacucho. We present a registry of ceramic forms and paste groups. Based on a stylistic level, a comparison is performed between the Intermediate and Late Horizon periods, which are defined by Katherine Schreiber and other authors for the valley of Sondondo and other surrounding areas. In addition, the stylistic comparison includes the revision of the ceramic collection originally collected by William Isbell in the 1970s, in an area to the north of our study. The results of this collection help identify stylistic and morphological characteristics of ceramic materials from the Canichi site. The results show the presence of various registered styles in the zone of Arequipa, specifically the Colca and Cotahuasi Valleys.